Characterization of the complete chloroplast genome sequence of Ulmus chenmoui (Ulmaceae), an endangered plant endemic to China. Issue 1 (2nd January 2019) - Zhang, Yunyan; Zhuang, Xin; Li, Junke; Li, Pengfu; Wang, Zhongsheng
Abstract: Ulmus chenmoui is of great ecological and horticultural importance and a national Class III protected plant endemic to China. However, previous studies of it suffered from insufficient genomic resources. Here, using the paired-end shotgun sequencing technology, we determined the complete chloroplast (cp) genome sequence of U. chenmoui . Our results showed the cp genome of U. chenmoui was 159, 371 bp long and displayed a typical quadripartite structure which consisted of a pair of inverted repeats (IRs) with a length of 26, 296 bp, separating by two single-copy regions (LSC, 88, 084 bp and SSC, 18, 695 bp). Besides, the cp genome of U. chenmoui contained 120 genes, including 83 protein coding genes, 29 transfer RNAs and eight ribosomal RNAs. Moreover, a maximum likelihood (ML) phylogenetic analysis based on the 13 cp genomes demonstrated the monophyly of Ulmaceae and U. chenmoui was closely related to Ulmus gaussenii .